Numerical Modelling and Simulation of the In-Plane Response of a Three-Storey Masonry-Infilled RC Frame Retrofitted with TRM - Filippou, Christiana; Kyriakides, Nicholas; Chrysostomou, Christis (My University, 2020)
A numerical study was conducted to investigate the in-plane behavior of a masonry-infilled reinforced concrete (RC) frame retrofitted with textile-reinforced mortar (TRM). A two-dimensional finite element model was developed using DIANA finite element analysis (FEA) software to simulate the 2: 3 scaled three-storey masonry-infilled RC frame retrofitted with TRM that was studied experimentally in the past. The three-storey structure used in the test was with a nonseismic design and detailing, and was subjected to in-plane displacement-control cyclic loading. The current study evaluates the capabilities of a representative numerical model to simulate the results of the experimental test, and after the calibration of the numerical model sensitivity analysis and parametric study were performed. In order to create an accurate numerical model, suitable constitutive models, based on the smeared crack approach, were used to characterize the nonlinear response of concrete, masonry infill, and TRM. The calibration of the models was based on the experimental results or inverse fitting based on optimizing the simulation of the response. The numerical model proved capable of simulating the in-plane behavior of the retrofitted masonry-infilled RC frame with good accuracy in terms of initial stiffness, and its deterioration, shear capacity, and cracking patterns. The calibrated model was then used to perform sensitivity analysis in order to examine the influence of infill-frame interface properties (tangential and normal stiffness) on the behavior of the retrofitted infilled frame. The numerical results showed that the gap opening is influenced significantly by the stiffness of the interface. In addition, a parametric study was performed in order to evaluate the importance of the full-bond condition between the TRM and the masonry-infilled RC frame. The numerical results indicate that the composite action between the TRM and the masonry-infilled RC frame improves the global stiffness and lateral resistance of the infilled frame, and it reduces the gap opening between the masonry infill and the RC frame.
Keywords: Infill; Masonry; Reinforced Concrete